2014
DOI: 10.1017/s104161021400101x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of burden in Alzheimer caregivers: confirmatory factor analysis and correlates of the Zarit Burden interview

Abstract: Background: To investigate dimensions of caregiver burden through factor analysis of the Zarit Burden Interview (ZBI), and to examine predictors of different dimensions of burden. Methods: Confirmatory factor analyses were performed on 395 Hong Kong Chinese Alzheimer caregivers to examine whether several proposed factor structures fit the data well. Subsequently, participants were split into two roughly equal subsamples, for the purpose of identifying the most optimal factor structure through exploratory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 37 publications
(62 reference statements)
3
45
1
Order By: Relevance
“…Our second largest factor was interpersonal relationship, which is labelled as interpersonal relation, 36 embarrassment/anger 15 or captivity 19 in other studies. In this study, we have named it interpersonal relationship, because all of these items describe the impact of caring for patients with schizophrenia on caregiver’s social life.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our second largest factor was interpersonal relationship, which is labelled as interpersonal relation, 36 embarrassment/anger 15 or captivity 19 in other studies. In this study, we have named it interpersonal relationship, because all of these items describe the impact of caring for patients with schizophrenia on caregiver’s social life.…”
Section: Discussionmentioning
confidence: 82%
“…The last factor was self-accusation and guilt comprising only two items (items 20 and 21). Although there were differences in the samples, this factor was also found in the Chinese context 19 21 22 as well as several other cultural contexts and appears to be the most stable or generalisable factor across samples and cultures. 15 39…”
Section: Discussionmentioning
confidence: 84%
“…The number of ZBI factors reported in these studies ranged from three to five, suggesting that additional factors beyond the three core components may represent variants of either role or personal strain. In support of this, a recent study in an Asian Chinese population similarly reported an optimal four-factor structure comprising two factors of role strain (captivity and loss of control), and one factor each of personal strain and self-criticism (items 20 and 21) ( 9 ).…”
Section: Introductionmentioning
confidence: 78%
“…Of note, a factor has consistently emerged in recent studies, known variously as: “self-criticism” ( 9 , 10 , 12 ), “guilt”( 13 15 ), “feelings of inadequacy” ( 16 , 17 ), and “worry about performance” ( 7 , 8 ). This factor highlights a distinct dimension of burden describing caregiver concerns about doing more (item 20) and doing a better job (item 21), either in isolation or in combination with other items ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chronic stress, occasionally exacerbated by unpredictable events, gives rise to recurrently elevated negative affect such as fatigue, anxiety, and depression, affecting health and the ability to carry out the caregiving duty. In fact, caregivers who are committed to their role, hence having high performance expectations on themselves, are likely to strain themselves and to feel sorry for not doing as much and as well as they would like (Cheng, Kwok, & Lam, 2014). Thus, caregivers have to learn how to regulate their emotions and are grateful for any assistance they get.…”
Section: Discussionmentioning
confidence: 99%